2001
DOI: 10.1117/12.436762
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional top-down metrology: a viable alternative to AFM or cross-section?

Abstract: Automated critical dimension (CD) metrology has long been known to have certain limitations. As a top down imaging technique, retrograde profiles, resist thickness loss and other process issues are difficult to detect with the standard production CD SEMs used throughout the industry. Tilting capability has recently added much needed degrees of freedom to CD SEMs, potentially opening the door to three dimensional metrology. Various methodologies can be used to interpret tilt image information. This paper invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[5] Several advantages of profile reconstruction using the technology have been reported. [6,7] In this paper, we demonstrate sidewall angle impact in etch bias. It is clearly shown that in order to control final CD, both resist linewidth and sidewall angles have to be monitored and controlled.…”
Section: Introductionmentioning
confidence: 97%
“…[5] Several advantages of profile reconstruction using the technology have been reported. [6,7] In this paper, we demonstrate sidewall angle impact in etch bias. It is clearly shown that in order to control final CD, both resist linewidth and sidewall angles have to be monitored and controlled.…”
Section: Introductionmentioning
confidence: 97%